2015
DOI: 10.1016/j.envres.2014.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Exposure determinants of cadmium in European mothers and their children

Abstract: The metal cadmium (Cd) is a widespread environmental pollutant with documented adverse effects on the kidneys and bones from long-term environmental exposure, but with insufficiently elucidated public health consequences such as risk of cardiovascular disease, hormone-related cancer in adults and developmental effects in children. This study is the first pan-European human biomonitoring project that succeeded in performing harmonized measurements of Cd in urine in a comparable way in mother-child couples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 24 publications
7
26
0
1
Order By: Relevance
“…High meat intake was associated with a decrease in blood Cd levels in nonsmoking women and all children. A similar finding was reported in nonsmoking women from 16 European countries (Berglund et al. 2015).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…High meat intake was associated with a decrease in blood Cd levels in nonsmoking women and all children. A similar finding was reported in nonsmoking women from 16 European countries (Berglund et al. 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Dietary determinants of other toxic elements, such as Cd and Pb are more diverse (Baeyens et al. 2014; Berglund et al. 2015; Castaño et al.…”
Section: Introductionmentioning
confidence: 99%
“…Our observation has confirmed that apart from the place of residence, some circumferences such as: the parental level of education and any occupational contact with heavy metals as well as parental smoking at home could be important determinants for assessment of children's exposure. Obtained results are again similar to the aforementioned multicenter publication [19].…”
Section: Resultssupporting
confidence: 80%
“…We adjusted for variables that have been associated with Cd exposure and that are recognized as influencing pregnancy and birth outcomes. Smoking status, highest educational attainment, and age were observed to be the strongest predictors of urinary Cd concentrations in a recent study of women and/or children across 16 European countries (Berglund et al. 2015).…”
Section: Methodsmentioning
confidence: 96%